Pemberdayaan Mahasiswa Beretos Digital: Pemanfaatan AI Bertanggung Jawab dalam Meningkatkan Pembelajaran di Perguruan Tinggi - Yustina Sri Ekwandari; Aprilia Triaristina; Valensy Rachmedita (Pakis Journal Institute, 2026)
The rapid development of Artificial Intelligence (AI) technology has brought significant changes to higher education. Empowering students to use AI responsibly has become an essential step in improving the quality of learning at the university level. This study aims to explore how AI can serve as an effective supporting tool in the learning process, particularly in the field of history, which requires deep analytical and interpretive skills in working with historical sources Through a training program for fourth-semester students of the History Education Study Program, participants were equipped with a foundational understanding of AI and guidance on applying it ethically and critically in historical source analysis and academic writing. Students were also trained to use AI for historical research, paper writing, research question formulation, and information verification to ensure academic accountability The program employed a participatory approach covering three stages: AI theory introduction, hands-on practice, and mentoring with evaluation. Results showed a significant improvement in students' understanding of AI, their ability to use it wisely, maintain academic integrity, and enhance the quality of history learning. Responsible AI use was also found to foster the development of critical and analytical thinking skills among students Students gained not only technical competencies but also ethical awareness regarding the boundaries of AI use to uphold academic honesty. This study recommends that higher education institutions integrate AI literacy training into their curriculum, enabling students to navigate the digital era in a more informed, critical, and responsible manner.